BI-LAMINATED ORAL DISINTEGRATING FILM FOR SYMPTOMATIC TREATMENT OF VIRAL NASOPHARYNGITIS: FORMULATION, CHARACTERIZATION, TASTE MASKING, AND STABILITY STUDIES - RIZK, MERNA A.; TEAIMA, MAHMOUD H.; ABDELMONEM, REHAB; EL-NABARAWI, MOHAMED A.; ELHABAL, SAMMAR FATHY (International Journal of Applied Pharmaceutics, 2024)
Objective: Nasopharyngitis (NP) is one of the most common upper respiratory tract infections (URTIs) brought on by viral infections and requires symptomatic treatment. In this study, a new approach to delivering drugs was developed, which is a bi-laminated oral disintegrating film (ODF) containing dextromethorphan hydrobromide (DEX), phenylephrine hydrochloride (PE), and methylcobalamin (MeCbl) to support the symptomatic treatment of NP. Yet, the extreme bitterness of DEX and PE required a taste-masking technique before ODF formulation to enhance patient compliance. Methods: Various complexing agents were tried at different ratios to mask the bitter taste of the drug(s). DEX-PE ODFs were formulated using the solvent casting procedure. A 31.21 full factorial design was performed to characterize DEX-PE ODFs, where the effects of polymer grade and plasticizer type were evaluated on the disintegration time (DT) and the percentage of drugs released after 10 min (Q10). Results: Complexation with maltodextrin (MD) and ion exchange resin (Kyron T-314) could successfully mask the bitter taste at a ratio of 1:2:2 of drugs, MD, and Kyron T-314, respectively. The ODF optimized formula (F4) recorded the least DT (5±0.5 s) and highest Q10 (96.7±2.1%) and (97.4±1.9%) for DEX and PE, respectively. F4 was then combined with the second film layer containing MeCbl to develop the bi-laminated ODF (B1), which was later evaluated and subjected to stability studies. Conclusion: In conclusion, a taste-masked, bi-laminated ODF could be successfully developed for the symptomatic treatment of NP.